HDTV and DRM: A Need of Further Regulation? - Georg Erber; Sven Heitzler (International Telecommunications Society (ITS), 2010)
In Germany, the TV broadcasting of the Winter Olympics 2010 marked the official start of high definition television (HDTV). However, the transition from standard to high definition television has been significantly hampered by inconsistent change management. While the large international movie and TV-series producers aim for increased (end-to-end) intellectual property rights protection on the one hand, the satellite and cable-TV network operators in coalition with the private commercial TV-broadcasters strive for advanced business models with increasingly differentiated pricing models on the other hand. The resulting technological requirements lead to rapid changes in technology, which in turn affects consumers and equipment manufacturers We analyze especially the related advancement of the systems and interface standards for encryption and copyright protection which are of central importance in this context, namely the so-called Common Interface (CI) and its enhancement to CI Plus as well as the HD+ satellite platform in order to identify critical issues for media regulators and competition authorities. Our analysis supposes that the German regulatory institutions' capabilities to deal with the issue of regulation against the background of efficient innovation management in a timely manner should be improved. This might also be an opportunity at the level of the European Community to set framework conditions based on principles similar to network neutrality to overcome the current deadlock in Germany and encourage regulatory reform. Especially consumer rights could be protected more effectively in a future regulatory framework for digital content distribution and in order to avoid a tragedy of the anti-commons being an impediment for the rapid transition to HDTV. Overall, our recommendations aim to contribute to achieve the goals of swift digitalization and transition to HDTV.
Keywords: L15; L51; L82; 330; HDTV; Innovation Management; Tragedy of the Anti-Commons